Strategi pemasaran pendidikan dalam menarik minat siswa di SMA muhammadiyah di Lombok - Mardiana, Lina (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2022)
Seeing the current situation, many educational institutions are standing, causing intense competition between institutions, so a business approach is also used in the world of education so that institutions can survive and be better known by many people. This study aims to find out how the educational marketing strategy for SMA Muhammadiyah Masbagik Kec. Masbagik Kab. East Lombok Province. NTB and what are the supporting and inhibiting factors in marketing? The method used by researchers is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. Data analysis through data reduction, data presentation, and data verification. To check the validity of the data through tests of credibility, transferability, dependability, and confirmability. The results of the study show that the educational marketing strategy in attracting students' interest in SMA Muhammadiyah Masbagik Kec. Masbagik Kab. East Lombok Province. NTB namely forming a marketing team, market identification, market segmentation by looking at the location of the area, outreach to schools, outreach to the community, distributing brochures, installing banners, and using social media such as Facebook, while the marketing mix has implemented 7 elements namely product, price, place, promotion, people, physical evidence, process. And the supporting factors when marketing is facilities and infrastructure as icons, marketing costs, teacher empowerment, school status, and flagship programs. Meanwhile, the inhibiting factor is the addition of quotas at public schools and a large number of public schools such as SMKs, community understanding, and the influence of friends.